Prevalence of Licit and Illicit Drugs Use during Pregnancy in Mexican Women - Larissa-María; Emilia Marchei; Maria Concetta Rotolo; Pietro Brunetti; Giulio Mannocchi; Aracely Acosta-López; Ruth-Yesica; Mary-Buhya; Simona Pichini; Oscar Garcia-Algar (MDPI AG, 2022)
For the first time, the present study employed hair testing to investigate the prevalence of classical drugs of abuse and new psychoactive substances use during gestation in a cohort of 300 Mexican pregnant women. An interview was conducted to collect data on sociodemographic aspects of the patients, and a 9 cm-long hair strand was taken from the back of the head of each mother one month after delivery. A validated ultra-high-performance liquid chromatography-high-resolution mass spectrometry method was used for the screening of classic drugs, new psychoactive substances, and medications in maternal hair. Out of 300 examined hair samples from pregnant women, 127 (42.3%) resulted positive for psychoactive substances: 45 (35.4%) for cannabis only, 24 (18.9%) for methamphetamine only, 13 (10.2%) for cocaine only, 1 (0.3%) for heroin, 1 for N-N-dimethyltryptamine (0.3%), 1 for ketamine (0.8%), and 35 (16.3%) for more than one psychoactive substance. Furthermore, seven samples (2.3%) resulted positive for new psychoactive substances (NPS): two samples for synthetic cannabinoids, two for synthetic cathinones, and three for nor-fentanyl, and 3.3% of women hair resulted positive for anticonvulsant, antidepressant, and antipsychotic medications. Finally, 83 women hair samples (27.7%) tested positive for nicotine. Nonsteroidal anti-inflammatory drugs (NSAIDs) and other painkillers (60.0%), medications for the treatment of nausea and vomiting (12.3%), antihistamines (8.7%) and nasal/sinus decongestants (6.7%), cough suppressants (5.0%), and bronchodilator agents (5.0%) were also detected in pregnant women hair. The gestational use of psychoactive substances and exposure to tobacco smoke, assessed by hair testing, were associated with a significantly younger age and with a low education grade of the mothers (p < 0.005). This study provides a significant preliminary indication of the under-reported gestational consumption of licit and illicit psychoactive and pharmacologically active drugs in a Mexican environment, showing the value of toxicological and forensic analyses in the global effort to determine the health risks caused by classic drugs and new psychoactive substances during pregnancy.